2021
DOI: 10.30630/joiv.5.2.398
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Requirements of Visually Impaired Users for Accessible Mobile E-book Applications

Abstract: Books are a medium for communicating information and in recent years have taken the electronic form called e-books. This shift has opened new opportunities for the visually impaired in overcoming their struggles with books in the traditional paper format. Yet, the National Federation of the Blind (NFB) claimed that many e-book applications do not meet needs of the visually impaired. Very few studies had investigated this subject matter hence paving the way for this current study to address the above research g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Al crear un REA se debe contemplar la accesibilidad de sus componentes. Uno de los requisitos básicos de usabilidad de libros electrónicos es que el texto debe estar claro para que las personas con discapacidad visual puedan ver las notas fácilmente (Hashim et al, 2021). El libro electrónico contempla el uso de letras Arial, Verdana y Atkinson Hyperlegible de 12 y 14 puntos, normal y semi negrilla, con la finalidad de hacerlo accesible.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Al crear un REA se debe contemplar la accesibilidad de sus componentes. Uno de los requisitos básicos de usabilidad de libros electrónicos es que el texto debe estar claro para que las personas con discapacidad visual puedan ver las notas fácilmente (Hashim et al, 2021). El libro electrónico contempla el uso de letras Arial, Verdana y Atkinson Hyperlegible de 12 y 14 puntos, normal y semi negrilla, con la finalidad de hacerlo accesible.…”
Section: Discusión Y Conclusionesunclassified
“…De acuerdo a la OMS se estima que 2,200 millones de personas aproximadamente viven con algún tipo de discapacidad visual (World Health Organization, 2021). Las personas con discapacidad visual dependen de la tecnología asistida para una mejor calidad de vida (Hashim et al, 2021). Existen diversas y variadas herramientas tecnológicas, por ejemplo, para el desarrollo de la lectoescritura está el sistema Braille, lectores de pantalla y reconocimiento de voz (Campos & Cartes-Velásquez, 2019), también se utilizan hardware, software y servicios (Kim et al, 2016).…”
unclassified
“…Thus, the findings revealed that the user interface of the e-procurement system needs additional improvements, such as page divisions for information search and easy position of buttons that are not difficult to find. Thus, the system should enable the users as learners to navigate from one page to another with easy [36]. Among such statements are:…”
Section: "System Has Privacy and Security With Password Protection" (...mentioning
confidence: 99%
“…To develop the application, the requirements of visually impaired users for accessible web applications were identified [12]. The application was designed to include features such as text-to-speech conversion, high contrast mode, keyboard navigation, and alternative text for images.…”
Section: Introductionmentioning
confidence: 99%